Investigating the factors of students lack of interest in physics at Kunduz University - Rahmanyar, Shafiullah; Faizi, Arafuddin; Shahryar, Shir Agha (Technium Education and Humanities, 2022)
The general purpose of this study is to investigate the factors of student’s slack of interest in physics at Kunduz University. The present research is based on an applied purpose, and in terms of nature and descriptive-survey method. Information and data were collected through a questionnaire. The statistical population in this study is all students of the physics department of the Faculty of Education of Kunduz University with 100 students. Because the statistical population in this study was sufficiently accessible and researchable, no sampling was used. The results obtained from this research in response to the students’ questionnaire hockey is that Kunduz University does not have a suitable educational environment, i.e. that Kunduz University has suitable repairs for education, amusement park, equipped dormitory, equipped library, internet club, gym, There is no green space… Also, at the level of shortage of professional professors or professional lecturers, the results of hockey research show that the physics department of Kunduz University does not have professional professors with sufficient experience and that is why their exam questions are not standard and they do not use any appropriate educational methods in psychology. They are also not aware so that they can understand the individual differences of students and adopt appropriate teaching methods.